Co-Culturing Rat Dorsal Root Ganglion Neurons With Rat Schwann Cells Protects Them Against the Cytotoxic Effects of Silver and Gold Nanoparticles. (January 2023) - Gao, Wenjuan; Lai, James C. K.; Leung, Solomon W.
Previous studies using monotypic nerve cell cultures have shown that nanoparticles induced neurotoxic effects on nerve cells. Interactions between neurons and Schwann cells may protect against the neurotoxicity of nanoparticles. In this study, we developed a co-culture model consisting of immortalized rat dorsal root ganglion (DRG) neurons and rat Schwann cells and employed it to investigate our hypothesis that co-culturing DRG neurons with Schwann cells imparts protection on them against neurotoxicity induced by silver or gold nanoparticles. Our results indicated that neurons survived better in co-cultures when they were exposed to these nanoparticles at the higher concentrations compared to when they were exposed to these nanoparticles at the same concentrations in monotypic cultures. Synapsin I expression was increased in DRG neurons when they were co-cultured with Schwann cells and treated with or without nanoparticles. Glial fibrillary acidic protein (GFAP) expression was increased in Schwann cells when they were co-cultured with DRG neurons and treated with nanoparticles. Furthermore, we found co-culturing with Schwann cells stimulated neurofilament polymerization in DRG neurons and produced the morphological differentiation. Silver nanoparticles induced morphological disorganization in monotypic cultures. However, there were more cells displaying normal morphology in co-cultures than in monotypic cultures. All of these results suggested that co-culturing DRG neurons with Schwann cells imparted some protection on them against neurotoxicity induced by silver or gold nanoparticles, and altering the expression of neurofilament-L, synapsin I, and GFAP could account for the phenomenon of protection in co-cultures.